Theory of economic statics - Brennan, Michael Joseph (Englewood Cliffs, N.J. : Prentice-Hall, 1970)
The book covers Theory of product demand. Theory of production and cost, Product pricing: pure competition. Product pricing: monopoly and nonpure competition. Resource pricing and income distribution. Normative economics.
Includes bibliographical references and index..
rpm 20/06/2017
Loans
Keywords: Economics; Microeconomics; Statics and dynamics (Social sciences)